2019
DOI: 10.5114/reum.2019.83240
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplant for progressive diffuse systemic sclerosis: procedural success and clinical outcome in 5-year follow-up

Abstract: Systemic sclerosis is an autoimmune connective tissue disease affecting both skin and internal organs. Progressive disease with multiple organ involvement is considered to have a poor prognosis. Treatment possibilities are limited, but certain patients may benefit from autologous hematopoietic stem cell transplantation (auto-HSCT).We report a case of a 30-year-old woman with progressive diffuse systemic sclerosis treated with parenteral cyclophosphamide with unsatisfactory results. Due to progression of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Both human bone aspirate concentrates and PRP containing CD34 + cells had similar therapeutic effects on bone regeneration [9]. The CD34 + hematopoietic stem cell is currently under investigation as a treatment for severe autoimmune diseases like alopecia universalis [6] and systemic sclerosis [10]. That study suggests the possibility of treating autoimmune diseases by the eradication of autoreactive cells.…”
Section: Discussionmentioning
confidence: 96%
“…Both human bone aspirate concentrates and PRP containing CD34 + cells had similar therapeutic effects on bone regeneration [9]. The CD34 + hematopoietic stem cell is currently under investigation as a treatment for severe autoimmune diseases like alopecia universalis [6] and systemic sclerosis [10]. That study suggests the possibility of treating autoimmune diseases by the eradication of autoreactive cells.…”
Section: Discussionmentioning
confidence: 96%
“…Pawlak-Bus, et al, reported recently the clinical outcome of a 5-year follow-up of a SScl patient that underwent AHSCT. The patient showed an improvement in exertion tolerance, partial regression of skin lesions and stabilization of pulmonary and cardiovascular changes [10]. Finally, in 2018, the American Society for Blood and Marrow Transplantation (ASBMR), based on high-quality evidence, recommended that AHSCT should be considered as a "standard of care" indication for SScl patients [11].…”
Section: Editorialmentioning
confidence: 99%
“…The most typical symptoms of SSc emerge from dermal and vascular lesions [30]. Pulmonary fibrosis and pulmonary artery hypertension are the leading causes of death in patients with SSc as pulmonary complications of SSc are one of the most challenging complications of SSc [18,31].…”
Section: Clinical Manifestations and Complications Of Sscmentioning
confidence: 99%